2003
DOI: 10.1073/pnas.1932554100
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in atherosclerosis: Bone biology and chronic inflammation at the arterial crossroads

Abstract: Dystrophic or ectopic mineral deposition occurs in many pathologic conditions, including atherosclerosis. Calcium mineral deposits that frequently accompany atherosclerosis are readily quantifiable radiographically, serve as a surrogate marker for the disease, and predict a higher risk of myocardial infarction and death. Accelerating research interest has been propelled by a clear need to understand how plaque structure, composition, and stability lead to devastating cardiovascular events. In atherosclerotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
320
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(343 citation statements)
references
References 60 publications
8
320
0
9
Order By: Relevance
“…Multiple mechanisms have been proposed to explain the etiology of vascular calcification, with bone biology, calcium homeostasis, and the inflammatory response having interactive roles [12,[43][44][45]. Specific mechanisms by which dietary calcium and vitamin D promote vascular calcification are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mechanisms have been proposed to explain the etiology of vascular calcification, with bone biology, calcium homeostasis, and the inflammatory response having interactive roles [12,[43][44][45]. Specific mechanisms by which dietary calcium and vitamin D promote vascular calcification are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium dysregulation is important in chronic diseases such as osteoporosis and atherosclerosis, as well as in nervous system disorders such as dementia and depression [9][10][11][12]. Calcification of vascular smooth muscle occurs with aging, renal disease, and atherosclerosis, and has been associated with brain lesions and cognitive impairment [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory role of osteoclastic-like cells in the maintenance of mineral homeostasis within the atherosclerotic arterial wall was postulated by Doherty et al 28 They suggested that vascular calcium deposition may be affected by the presence and activity of osteoclast-like cells, which are able to inhibit or even revert the ongoing calcification. However, mouse model studies indicated a procalcific influence of osteoclast-like cells on the cardiovascular system.…”
Section: Clinical and Biochemical Factors Associated With Os-mentioning
confidence: 99%
“…Ateroskleroz sürecinde rol alan kronik infl amasyon aynı zamanda vasküler kalsifi kasyona neden olan mekanizmaları da düzenlemektedir (6). Son dönemde yapılan çalışmalar VK gelişim sürecinde angiogenezin önemini ve osteoblast ve osteoklastların bu olaydaki etkilerini açıklığa kavuşturmuştur (7).…”
Section: Vasküler Kalsifi Kasyon Patogeneziunclassified